Projeto Prevenir: uma pesquisa acerca das mudanças no perfil das infecções por DST/AIDS, com a perspectiva de detectar pontos vulneráveis da prevenção - Rocha, Luciana Vilar de Sales (2007)
Rio Grande do Norte is among the Brazilian States where the tourism and sexual violence increasingly grow in the country, occupying 4th place in 2004. Associated to this fact, it comes the problematic one of the contamination of the women by Sexually Transmitted Disease (STD). Studies in Brazil have presented a considerable increase of the STDs, caused through lack of suitable protection in the sexual relationships. Due to the biological and psychosocial vulnerability, besides failures or inconsistencies in the condom use associated to the raised taxes of sexual activity with different partners, the STDs constitute the main risk of health. Many difficulties are found by the confrontation of this problem. In this context, this project had as aim to evaluate the vulnerability of this population of sexually active women in Natal-RN Ponta Negra neighbourhood to the infections by STDs, such as, Candida sp., Vaginoses Bacterial, Trichomonas Vaginalis and Chlamydia sp., arisen with the explosion of the sex market, showing a current statistical panorama. It was possible to detect vulnerable points in prevention through patient anamnesis, where the study it showed: high number of partners (8,3% with more than five), low age of first relationship and not the use of condoms (31,8% sometimes use and 45,8% had not used in the first relationship). Already consolidated by the preventive cytopathologic examination, these data were strengthened by high incidence of causing agents of STDs (58,6%). In this way, it is clear that the sexuality must to be thought on the context of the deep economic and socio-cultural transformations in which pass societies, and mainly the ones concerning to the sexuality exercise and to the sex market. With the profile change of the infections, new demands are placed in relation to the risk factors. Therefore, it can be concluded that the prevention vulnerable points detected as more important had been the deficiency in self-perception and wareness of the risk existence among the studied women